Otimização de estruturas de cascas com carregamento dinâmico com modelagem via NURBS - Gomes Filho, Hélio (2018)
This work presents the optimization of the thickness of shells subjected to static and dynamic loading. The structural analysis is done by the Finite Element Method. A combination of the CST elements (Constant Strain Triangle) and DKT (Discrete Kirchhoff Theory) was used as the shell element, thus forming an element with fifteen degrees of freedom (three nodes with five degrees of freedom each) . The finite element mesh is generated for a unitary square domain and transformed for the domain analyzed by means of NURBS functions. These functions model the domain (surface) in study. We developed routines to optimize the thickness of the shell elements using the SQP (Sequential Quadratic Programming) method available as a tool of the Matlab software, using as constrains the maximum displacement and the minimum vibration frequency. Several examples were used to validate static and dynamic analysis routines, comparing results with consecrated literature and with models developed in the ANSYS Workbench software. As a final example, they propose a modeling for the Pampulha Church.